Development of Community Led Renewable Energy Projects. Issue 1657 (22nd January 2014) - Mawyin, Jose A.; Krzywoszynska, Anna; Buckley, Alastair; Gregson, Nicky; Watson, Matt; Holmes, Helen; Chiles, Prue; Lidzey, David
ABSTRACT: The United Kingdom aims to decarbonize its national electricity generation in order to transition to a low carbon economy. Solar, wind, hydro and thermal energy conversion are renewable alternatives to fossil fuels and are currently being explored that may form part of the future generation mix of the country. How does materials scientist's work addressing energy research challenges for solar and storage (for example) translate into the adoption of new technology? How appropriate are the technology usage visions of the scientists? How can technology users better inform the materials science motivations? This report will focus on how a multidisciplinary team of researchers from the Universities of Sheffield and University of Durham, community members and industry representatives are jointly developing renewable energy projects to try to answer these and other questions. The history of the project will be presented as well as the methodology used to collaboratively engage the community participants. This work is supported by a grant provided by the Engineering and Physical Sciences Research Council (EPSRC) of the United Kingdom.